TEACHING ENGLISH WITH MIXED METHODS - Egamberdiyeva, Zilola (Журнал иностранных языков и лингвистики, 2021)
ABSTRACT: this article describes the communicative teaching English language. This article shows combining two types which are traditional and modern methods of teaching and how we can make our teaching very effective KEYWORDS atmosphere, evaluated, traditional, modern, Innovative.